2012
DOI: 10.3109/19401736.2012.674120
|View full text |Cite
|
Sign up to set email alerts
|

Identification of sequence polymorphisms in the D-loop region of mitochondrial DNA as a risk factor for lung cancer

Abstract: Accumulation of single nucleotide polymorphisms (SNPs) in the displacement loop (D-loop) of mitochondrial DNA (mtDNA) may be associated with an increased cancer risk. We investigated the lung cancer risk profile of D-loop SNPs in a case-controlled study. The minor alleles of nucleotides 235A/G and 324A/G were associated with an increased risk for lung cancer patients. The minor alleles of the nucleotides 151C/T, 200A/G, 524C/CA, and 16274G/A were specifically associated with the cancer risk of squamous cell ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 32 publications
0
14
1
Order By: Relevance
“…We have identified outcome-associated SNPs of these regions in other cancers 21,27. The allele 315 was identified as a cancer risk-associated SNP for NHL, and allele 151 was identified as a cancer risk-associated SNP for non-small cell lung cancer in previous study 19,31. Our data imply the important role of HVII region in modifying the onset age of cancer.…”
Section: Discussionmentioning
confidence: 54%
“…We have identified outcome-associated SNPs of these regions in other cancers 21,27. The allele 315 was identified as a cancer risk-associated SNP for NHL, and allele 151 was identified as a cancer risk-associated SNP for non-small cell lung cancer in previous study 19,31. Our data imply the important role of HVII region in modifying the onset age of cancer.…”
Section: Discussionmentioning
confidence: 54%
“…Selected SNPs in the D-loop region have been examined for their ability to predict cancer risk and outcome in many types of tumor, including esophageal squamous cell carcinoma13, hepatocellular carcinoma14, oral squamous cell carcinoma15, lung cancer16. The present study has extended previous analyses to determine the relationship between age-at-onset and germline SNPs in a continuous sequence of mtDNA between nucleotides 16190 and 583 in RCC patients.…”
Section: Discussionmentioning
confidence: 80%
“…An increase of mutations and SNPs in the mitochondrial D-loop region have been reported in a variety of cancers, including esophageal squamous cell carcinoma (17), hepatocellular carcinoma (18), oral squamous cell carcinoma (19) and lung cancer (20). In this case-control study, cancer risk-associated SNPs for RCC were investigated in a continuous sequence of mtDNA between nucleotides 16190 and 583, and 5 SNP sites, comprising 16293, 262, 488, 16298 and 16319, were identified.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the 16293 site is associated with the risk of developing hepatocellular carcinoma (18) and the 16298 site is associated with resistance to small-cell lung carcinogenesis (20). The D-loop is the most variable region in mtDNA.…”
Section: Discussionmentioning
confidence: 99%